The Effect of Local Original Revenue, General Allocation Funds, and Capital Expenditure on Regional Financial Independence (Case Study of Regency/City on the Coastal Line of Java Island 2020-2024) - Aqif Fadil; Purwanto (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
Regional financial independence is an important indicator of the successful implementation of regional autonomy. However, the level of financial independence in most regencies and municipalities located in the coastal areas of Java remains relatively low due to their high dependence on transfers from the central government. This condition indicates the need to optimize regional revenue sources and manage expenditure effectively in order to strengthen regional fiscal capacity. This study aims to analyze the effects of Local Own-Source Revenue (PAD), the General Allocation Fund (DAU), and Capital Expenditure on Regional Financial Independence in regencies and municipalities located in the coastal areas of Java during the 2020–2024 period, both partially and simultaneously. This study employed a quantitative method with descriptive and verificative approaches. The data used were secondary data obtained from local government financial reports and publications issued by the Directorate General of Fiscal Balance (DJPK). The data were analyzed using panel data regression to examine the relationships between the independent and dependent variables. The results indicate that Local Own-Source Revenue has a positive and significant effect on Regional Financial Independence, whereas the General Allocation Fund has a negative and significant effect. Capital Expenditure has a positive effect on Regional Financial Independence. Simultaneously, PAD, DAU, and Capital Expenditure have a significant effect on Regional Financial Independence. The contribution of this study lies in providing empirical evidence regarding the factors that influence Regional Financial Independence in the coastal areas of Java, which have diverse economic and fiscal characteristics. The findings imply that local governments should optimize PAD, reduce dependence on central government transfers, and allocate Capital Expenditure to productive sectors in order to strengthen fiscal independence and support sustainable regional development.